MENINGKATKAN KOSAKATA BENDA MELALUI MEDIA PEMBELAJARAN WORD SQUARE BAGI ANAK TUNARUNGU - Zikra, Rafika; Z, Martias (Jurnal Penelitian Pendidikan Khusus, 2021)
This research is motivated by a deaf student in seventh grade who truly lacks of vocabulary. Therefore, it is really needed for the student, a method or learning media that can enrich vocabulary. By doing this research, it can be proven that word square as teaching media can enrich the vocabulary for the deaf student in seventh grade in SLBN 1 Bukittinggi. The Method that is used is single subject researh (ssr) with A-B-A design through graphic visual data analysis. The result of the research shows that, from the analysis of sixteen meetings, on baseline (A1) condition it shows 10%, 16,66%, 16,66%, 16,66%. In the intervention  condition (B) , it results 66,66%, 70%, 83,33%, 93,33%, 93,33%, 96,66%, 96,66%, 96,66%.. In the last condition, which is baseline (A2) it results 96,66%, 96,66%, 96,66%, 96,66%. The result of this research states that word square learning media can enrich vocabulary, which is noun for the deaf student.